2018
DOI: 10.1002/jcp.27549
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐141‐3p inhibits retinal neovascularization and retinal ganglion cell apoptosis in glaucoma mice through the inactivation of Docking protein 5‐dependent mitogen‐activated protein kinase signaling pathway

Abstract: Retinal neovascularization occurs in various ocular disorders including proliferative diabetic retinopathy and secondary neovascular glaucoma, resulting in blindness. This paper aims to investigate the effect of microRNA‐141‐3p (miR‐141‐3p) on retinal neovascularization and retinal ganglion cells (RGCs) in glaucoma mice through the Docking protein 5 (DOK5)‐mediated mitogen‐activated protein kinase (MAPK) signaling pathway. Chip retrieval and difference analysis were used for the potential mechanism of miR‐141‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…24 In our study, we found that the activity and expression of caspase-1 and IL-1b were significantly increased in HG-treated HRMECs and clinical vitreous samples, suggesting that pyroptosis is involved in the pathogenesis of DR. Increasing evidence has demonstrated that miRNAs function as effective biomarkers or therapeutic targets, 25 and many miRNAs have been shown to have important roles in DR progression. 26,27 In our study, we initially investigated the role in DR of miR-590-3p, which is an inflammation-related miRNA 16,18,28 that may participate in the progression of pyroptosis. Our results indicated that the miR-590-3p inhibitor induced pyroptosis, which is consistent with the HG-induced condition.…”
Section: Discussionmentioning
confidence: 99%
“…24 In our study, we found that the activity and expression of caspase-1 and IL-1b were significantly increased in HG-treated HRMECs and clinical vitreous samples, suggesting that pyroptosis is involved in the pathogenesis of DR. Increasing evidence has demonstrated that miRNAs function as effective biomarkers or therapeutic targets, 25 and many miRNAs have been shown to have important roles in DR progression. 26,27 In our study, we initially investigated the role in DR of miR-590-3p, which is an inflammation-related miRNA 16,18,28 that may participate in the progression of pyroptosis. Our results indicated that the miR-590-3p inhibitor induced pyroptosis, which is consistent with the HG-induced condition.…”
Section: Discussionmentioning
confidence: 99%
“…A recent experiment utilized 12-week DBA/2J mice that received an injection of glutamate to induce RGC excitotoxicity. Intravitreal delivery of a virus expressing miR-141-3p led to a significant increase in RGC survival along with downregulation of apoptotic signalling pathways such as Bax and caspase-3 (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Slc2a1 abundance in HIF1α signaling plays a key role in promoting neuronal survival by mediating the endogenous protective responses after hypoxia-ischemia. In glaucoma mice, decreased HIF1α expression is observed to be correlated with RGC loss [ 56 ]. H 2 S regulates HIF1 factors in different patterns, depending on different cell types and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%